Hematologic and serum biochemistry values in free-living spectacled caiman (Caiman crocodilus) in Madre de Dios, Peru - Carlos Erazo, Nancy (2017)
The aim of the study was to determine the values of hematologic and serum biochemistry in free-living spectacled caiman (Caiman crocodilus) in Madre de Dios, Peru. A total of 30 individuals (26 males and 4 females) were captured in the banks of the Madre de Dios river. Blood sampled were collected from the dorsal branch of the cranial vein. The following results were found: RBC 1.45±0.97 x 106/μl, PCV 22.63±4.16%, Hb 7.86±2.10 g/dl, MCV 190.6±76.9 fl, MCH 63.49±20.96 pg, MCHC 34.96±7.80 g/dl, WBC 13.18±5.85 x 103/μl, eosinophils 1.54±1.21 x 103/μl, basophils 1.31±1.20 x 103/μl, lymphocytes 5.77±4.03 x 103/μl, monocytes 0.17±0.38 x 103/μl, heterophiles 2.16±2.59 x 103/μl, ALT 48.59±14.34 U/L, AST 114.0±28.5 UI/L, GGT 1.8±1.6 UI/L, creatinine 0.51±0.35 UI/L, cholesterol 101.8±42.3 UI/L, glucose 98.1±30.7 mg/dL total protein 5.01±1.00 g/dl, albumin 1.65±0.29 g/dL, globulins 3.13±1.08 g/dL, calcium 10.11±1.63 mg/dL, phosphorus 6.44±1.09 mg/ml. Significant differences were found by sex for MVC and MCHC.